2014
DOI: 10.1017/s0022381614000528
|View full text |Cite
|
Sign up to set email alerts
|

Who Asks For Voter Identification? Explaining Poll-Worker Discretion

Abstract: As street-level bureaucrats, poll workers bear the primary responsibility for implementing voter identification requirements. Voter identification requirements are not implemented equally across groups of voters, and poll workers exercise substantial discretion in how they apply election law. In states with minimal and varying identification requirements, poll workers appear to treat especially minority voters differently, requesting more stringent voter identification. We explain why poll workers are differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“… Our argument is similar to Atkenson et al () who find that poll workers differ from other types of bureaucrats.…”
supporting
confidence: 92%
“… Our argument is similar to Atkenson et al () who find that poll workers differ from other types of bureaucrats.…”
supporting
confidence: 92%
“…Others have shown that a lack of identification is particularly acute among the minority population, the poor, and the young (Ansolabehere 2014; Barreto, Nuno, and Sanchez 2009;Barreto and Sanchez 2014; but see Alvarez, Bailey, and Katz 2011). 3 A different set of researchers has attempted to assess whether the existing laws are applied evenly and have found that poll workers disproportionately ask minorities for identification (Ansolabehere 2009;Atkeson et al 2010Atkeson et al , 2014Cobb, Greiner, and Quinn 2012;Rogowski and Cohen 2014;White, Nathan, and Faller 2015). There is even some evidence that in a small set of cases provisional ballots that should have been counted have ultimately not been included in vote tallies (Pitts 2013).…”
Section: Evaluating Voter Id Lawsmentioning
confidence: 99%
“…The temporary nature of their work means poll workers have less opportunity to develop a shared set of organizational norms to ensure consistent running of elections (Atkeson et al, 2014). Whereas career bureaucrats may develop a shared commitment to the quality of an agency, poll workers do not consistently have this opportunity.…”
Section: Poll Workers As Street-level Bureaucratsmentioning
confidence: 99%